Particle transport induced by electrostatic wave fluctuations. (September 2015) - Rosalem, K C; Roberto, M; Caldas, I L
Abstract: Particle transport driven by electrostatic waves at the plasma edge is numerically investigated, for large aspect ratio tokamaks, by considering a kinetic model derived from guiding-center equations of motion. Initially, the transport is estimated for trajectories obtained from differential equations for a wave spectrum generated by a dominant spatial mode and three time modes. Then, in case of infinite time modes, the differential equations of motion are used to introduce a symplectic map that allows to analyze the particle transport. The particle transport barriers are observed for spatial localized dominant perturbation and infinite modes. In presence of infinite spatial modes, periodic islands arise in between chaotic trajectories at the plasma edge.